Titanium alloy database - Kaufman, J. G. 1931- (Knovel Corp., 2012)
"The Knovel Titanium Alloy Database is a comprehensive summary of typical or representative values and, where available, estimated minimum values of the mechanical and physical properties of a wide variety of commercial titanium alloys in various production conditions at various temperatures."--HTML introd. (viewed Jan. 23, 2013).